Predictors of care for patients with cancer of unknown primary site in three Australian hospitals. Issue 5 (3rd November 2017) - Tan, Simon Y. S.; O'Neill, Siobhan; Goldstein, David; Ward, Robyn L.; Daniels, Benjamin; Vajdic, Claire M.
Abstract: Aim: Cancer of unknown primary site (CUP) is a medically challenging malignancy with a poor prognosis. We describe an incident tertiary CUP patient cohort and identify factors predictive of specific types of health care. Methods: We reviewed the medical records of 217 patients diagnosed with CUP (2006–2011) in three public hospitals in New South Wales, Australia. We systematically abstracted data and performed multivariable logistic regression to identify factors predictive of tumor biopsy, surgery, chemotherapy, radiotherapy and palliative care. Results: The median age at CUP diagnosis was 75 years (range 23–98) and 52% were male. The most common mode of presentation was emergency department admission (57%). Serum tumor markers were performed in 42%, fine needle aspiration alone in 15% and core biopsy in 52%. Younger age, health service referral, oncologist review and a family history of cancer predicted receipt of a biopsy (77%). Cancer‐related surgery (17%) was more likely in younger patients, those presenting with pain, and those with single lymph node metastases. Younger age and good performance score predicted receipt of chemotherapy (22%). The location of metastases predicted receipt of radiotherapy (28%). Older age, emergency presentation, poor performance score and no oncology review predicted receipt of palliative care only (52%); 77% were referred for palliative care during hospitalization. Conclusion: The determinants of care were generally consistent with international CUP clinical guidelines. Areas of future research include potential underinvestigation and undertreatment of older patients, overuse of certain low‐value diagnostic tests, suboptimal use of immunohistochemistry and mammography and underreferral to palliative care.